Daily Fruit-Vegetable Consumption, Morbidity Pattern and Healthcare Seeking Behaviour in General Adults Living on the Outskirts of a Sub-Metropolitan City - Jitendra Kumar Singh; Kshitiz Shrestha; Alina Poudel; Raman Mishra; Rajan Paudel; Dilaram Acharya (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Fruits and vegetables are essential for a healthy diet, yet global consumption remains below recommended levels, particularly in developing countries like Nepal, increasing the risk of non-communicable diseases. This study examines fruit and vegetable intake, morbidity patterns, and healthcare-seeking behavior among adults in the outskirts of Janakpur Sub-Metropolitan. Materials and Methods: A community-based cross-sectional study was conducted between September 2024 and December 2024 with a sample of 466 general adult population aged 18 years and above. Data were collected through face-to-face interviews with structured questionnaire selected through multistage random sampling. Binary logistic regression was employed to identify predictors of fruit and vegetable consumption. Results: Out of 466 participants, only 15.23% of participants consumed fruit on a daily basis. Majority (68.3%) sought care from qualified doctors followed by qualified paramedical (23.8%) and few (7.9%) sought care from non-health professionals. Further, people who sought health care from qualified doctor had a significantly higher likelihood of consuming leafy vegetable 2-3 times per week. Similarly, Participants with anaemia were significantly less likely to consume leafy vegetable frequently. Conclusion: This study highlights the low consumption of fruits and vegetables, with a higher likelihood of consuming leafy vegetables among those who seeks care from qualified medical doctors. However, frequent consumption of leafy greens has been observed to be greatly constrained among anaemic. Public health education should focus on the importance of fruit and vegetable intake and its impact on overall health.